2021
DOI: 10.1186/s12917-021-02925-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ORF5 sequences of Porcine Reproductive and Respiratory Syndrome virus (PRRSV) circulating within swine farms in Costa Rica

Abstract: Background Worldwide, Porcine Reproductive and Respiratory Syndrome (PRRS) is among the diseases that cause the highest economic impact in modern pig production. PRRS was first detected in Costa Rica in 1996 and has since then severely affected the local swine industry. Studies of the molecular characterization of circulating strains, correlation with clinical records, and associations with pathogens associated with Porcine Respiratory Disease Complex (PRDC) have not been done in Costa Rica. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Each 25 µL-reaction contained 7 µL of RNA and 18 µL of Mix PRRS European (EU) and North American (NA) strains (EU/NA) from the kit. The RT-PCR reactions were carried out on a 7500 Fast Real-Time PCR System, laptop, QST (Life Technologies, Thermo Fisher Scientific Inc., Waltham, MA, USA) in a 96-well format according to the manufacturer's recommendations ( Moreover, the open reading frame 5 region (ORF5) of all positive serum samples were sequenced using Sanger technology as previously described [21] and some sequences coming from tongue exudate (from farms 4, 50, 36, 6, 9, and 52) were also sequenced for this study.…”
Section: Diagnostic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each 25 µL-reaction contained 7 µL of RNA and 18 µL of Mix PRRS European (EU) and North American (NA) strains (EU/NA) from the kit. The RT-PCR reactions were carried out on a 7500 Fast Real-Time PCR System, laptop, QST (Life Technologies, Thermo Fisher Scientific Inc., Waltham, MA, USA) in a 96-well format according to the manufacturer's recommendations ( Moreover, the open reading frame 5 region (ORF5) of all positive serum samples were sequenced using Sanger technology as previously described [21] and some sequences coming from tongue exudate (from farms 4, 50, 36, 6, 9, and 52) were also sequenced for this study.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…A sample was considered positive if the RT-PCR PRRSV Ct value was equal to or below 35. Moreover, the open reading frame 5 region (ORF5) of all positive serum samples were sequenced using Sanger technology as previously described[21] and some sequences coming from tongue exudate (from farms 4, 50, 36, 6, 9, and 52) were also sequenced for this study.…”
mentioning
confidence: 99%
“…Unlike other studies which focused on a single or on few clusters [ 13 ] or subgroups or lineages [ 14 , 22 , 34 ] or limited to a few farms [ 8 ] our study covered all wild-type clusters found over a 10 year-period at the provincial level. Furthermore, each cluster was described based on its detection in at least one of pig site within a year instead of the number of detections, in order to prevent the influence of repeated sampling of the same strain within a herd during the same year.…”
Section: Discussionmentioning
confidence: 99%
“…GP5 is also proposed to be the primary target for neutralization, of which importance is supported by the identification of a neutralizing epitope and the discovery of neutralization-resistant mutants in GP5 [ 12 , 26 , 30 , 31 ]. Therefore, the genetic analysis, including the nucleotide acid mutations and fragments recombination of ORF5, portends a potential evolutionary direction of PRRSV [ 6 , 32 ]. The two novel strains GD-H1 and GD-F1 in our study both have recombinant fragments derived from NADC30 and NADC34-like strains, suggesting that it may lead to the immune escape of the PRRSV and bring more difficulties to the prevention and control of PRRS.…”
Section: Discussionmentioning
confidence: 99%